PENGARUH PENGAWASAN TERHADAP DISIPLIN KERJA PEGAWAI BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN BERAU - Purwoko, Agus (STIE Muhammadiyah Tanjung Redeb, 2018)
The purpose of this study is to know clearly about the supervision’s effect towards  the work discipline of employees of the Regional Disaster Management Agency of Berau District. The analysis tools that used in this study was : Product Moment correlation coefficient, simple linear regression equation and hypothesis testing with Test t.             Based on the results of the research shown  that the simple linear regression equation on the supervision’s effect towards  the work  discipline of employees of the Regional Disaster Management Agency of Berau District was Y = 7.05 + 0.76X. The value of product moment correlation coefficient was  0,9101, so r> 0 (0,9101> 0) hence there was  positive linear correlation between supervisory variable and work discipline variable. In this case the close relationship between the two variables can be interpreted as very high correlation (in the scale of 0.800-1000). The value of t arithmetic was 14.90 while the value of t table was  2.0129. So that the value of t arithmetic greater than t table (14,90> 2.0129), then the hypothesis proposed in this study accepted or proved that the supervision has a significant effect on the work discipline of employees of the Regional Disaster Management Agency of the District of Berau.